PENGARUH REKRUTMEN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MAXI MULTI MANDIRI DI TANGERANG SELATAN - Wira Haga Muhammadin; Umar Hanis (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of recruitment and job training on employee performance at PT Maxi Multi Mandiri South Tangerang, both partially and simultaneously. The method used is descriptive quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 63 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, coefficient of determination analysis, correlation coefficient analysis and hypothesis testing. The results of this research are that recruitment has a positive and significant effect on employee performance with the regression equation Y = Y = 11.354 + 0.663X, the correlation value obtained is 0.655, meaning that the two variables have a strong level of relationship. The coefficient of determination value is 42.9%. Hypothesis testing obtained a calculated t value > t table or (6.767 > 2.00030). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant influence of recruitment on employee performance. Job training has a positive and significant effect on employee performance with the regression equation Y = 9.807 + 0.829X, the correlation value obtained is 0.743, meaning that the two variables have a very strong level of relationship. The coefficient of determination value is 55.2%. Hypothesis testing obtained a calculated t value > t table or (8.672 > 2.00030). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant influence of job training on employee performance. Recruitment and job training simultaneously have a positive and significant effect on employee performance with the regression equation Y = 3.303 + 0.348X1 + 0.611X2, the correlation value or level of relationship between the independent variable and the dependent variable is 0.795, meaning it has a very strong relationship. The coefficient of determination or contribution of simultaneous influence is 63.2%, while the remaining 36.8% is influenced by other factors. Hypothesis testing obtained calculated F value > F table (51.624 > 3.15). Thus H0 is rejected and H3 is accepted. This means that there is a significant influence simultaneously on recruitment and job training on employee performance.